Microbiome and Culture Based Analysis of Chronic Rhinosinusitis Compared to Healthy Sinus Mucosa - Koeller, Kerstin; Herlemann, Daniel P. R.; Schuldt, Tobias; Ovari, Attila; Guder, Ellen; Podbielski, Andreas; Kreikemeyer, Bernd; Olzowy, Bernhard (Frontiers in Microbiology, 2018)
The role of bacteria in chronic rhinosinusitis (CRS) is still not well understood. Whole microbiome analysis adds new aspects to our current understanding that is mainly based on isolated bacteria. It is still unclear how the results of microbiome analysis and the classical culture based approaches interrelate. To address this, middle meatus swabs and tissue samples were obtained during sinus surgery in 5 patients with CRS with nasal polyps (CRSwNP), 5 patients with diffuse CRS without nasal polyps (CRSsNP), 5 patients with unilateral purulent maxillary CRS (upm CRS) and 3 patients with healthy sinus mucosa. Swabs were cultured, and associated bacteria were identified. Additionally, parts of each tissue sample also underwent culture approaches, and in parallel DNA was extracted for 16S rRNA gene amplicon-based microbiome analysis. From tissue samples 4.2 ± 1.2 distinct species per patient were cultured, from swabs 5.4 ± 1.6. The most frequently cultured species from the swabs were Propionibacterium acnes, Staphylococcus epidermidis, Corynebacterium spp. and Staphylococcus aureus. The 16S-RNA gene analysis revealed no clear differentiation of the bacterial community of healthy compared to CRS samples of unilateral purulent maxillary CRS and CRSwNP. However, the bacterial community of CRSsNP differed significantly from the healthy controls. In the CRSsNP samples Flavobacterium, Pseudomonas, Pedobacter, Porphyromonas, Stenotrophomonas, and Brevundimonas were significantly enriched compared to the healthy controls. Species isolated from culture did not generally correspond with the most abundant genera in microbiome analysis. Only Fusobacteria, Parvimonas, and Prevotella found in 2 unilateral purulent maxillary CRS samples by the cultivation dependent approach were also found in the cultivation independent approach in high abundance, suggesting a classic infectious pathogenesis of odontogenic origin in these two specific cases. Alterations of the bacterial community might be a more crucial factor for the development of CRSsNP compared to CRSwNP. Further studies are needed to investigate the relation between bacterial community characteristics and the development of CRSsNP.